The Law on business organization : partnerships and corporations - Torres, Justo P., Jr. (Manila, Philippines : Rex Book Store, 2008)
This book has been prepared for use in colleges and universities, in a course on partnership and private corporation. The author has endeavored to present the fundamental concepts and principles governing partnership and private corporations in a simple and functional way to help students not well-versed in legal technicalities to understand the legal rules applicable to business organizations.
Keywords: CORPORATION LAW -- PHILIPPINES